2001
DOI: 10.1097/00129492-200103000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Results of Ossiculoplasty in Austin-Kartush Group A Patients

Abstract: Cumulative data from several authors show that -50% of patients undergoing partial ossiculoplasty have a postoperative air-bone gap of 0 to 10 dB, and 80% have a postoperative air-bone gap of 0 to 20 dB. Equally good results may be achieved with autograft (no difference was found between interposition of the incus or the head of the malleus), homograft, or alloplastic partial prostheses. With alloplastic total prostheses, 36% of patients have a postoperative air-bone gap of 0 to 10 dB, and 74% have a postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…13 Hence, the most common reconstruction model for an ossicular defect is a type III tympanoplasty. 14,15 In this type of tympanoplasty, whether the stapes is movable or fixed is a crucial factor in obtaining improved hearing results. For patients with mobile stapes, hearing results have been shown to be significantly better than for those with fixed stapes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Hence, the most common reconstruction model for an ossicular defect is a type III tympanoplasty. 14,15 In this type of tympanoplasty, whether the stapes is movable or fixed is a crucial factor in obtaining improved hearing results. For patients with mobile stapes, hearing results have been shown to be significantly better than for those with fixed stapes.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,15,[19][20][21][22] Long-term follow up requires commitment and resources that can be difficult to achieve. To our knowledge, reports on the long-term follow up for type III tympanoplasty are rare; the rates of post-operative ABG closure to within 20 dB range from 48 to 81.3 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…25 of our patients had a post op air bone gap of 0 to 20 dB hence 83.33 percent of the patients had an air bone gap of 0 to 20 dB post op which can be compared to Iiurato et al who in their retrospective review of large series of Austin-Kartush type A ossiculoplasties of various surgeons showed air-bone gap of 0 to 10 dB for 20% to 68% of patients and of 0 to 20 dB for 54% to 93% of patients post-surgery. 17 The above observations remained unchanged over the next 3 months and these patients had similar hearing threshold even 6 months post-surgery, this is a testament to the survival of the cartilage in the middle ear and also to the stability of the assembly for this period of time. Extrusion of the cartilage was not noticed in any of the patients and hence is not noted as a complication.…”
Section: Discussionmentioning
confidence: 59%
“…11 Shinohara et al 12 reported 68% success rates with PORP where only the incus needs to be replaced This compares with 46% of TORP where incus and stapes superstructure are absent. Palva and Ramsay, 13 looked at the outcome of 281 myringoplasties in their department The closure rate in Palva s hands was 97%, while in hands of other members it was 74%.…”
Section: Discussionmentioning
confidence: 99%